2017
DOI: 10.1007/s10800-017-1049-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of aluminum fluoride as a new cathode material for lithium-ion batteries

Abstract: Graphical Abstract Capacity of AlF 3 exceeds 900 mAh g −1 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…(inset) pore size distribution analysis of the degassed C-AlF3 composite material using the QSDFT method for slit/cylinder-like shape pores in the N 2 desorption data. 18…”
Section: Porosity and Related Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…(inset) pore size distribution analysis of the degassed C-AlF3 composite material using the QSDFT method for slit/cylinder-like shape pores in the N 2 desorption data. 18…”
Section: Porosity and Related Propertiesmentioning
confidence: 99%
“…As briefly mentioned in the introduction, AlF 3 can be effectively used in the field of electrochemical energy storage and more specifically in the technology of Li-ion batteries. In this respect, AlF 3 can act as a promising cathode material [18], enhance the performance of graphite anodes [19] as well as improve the electrochemical cycling of Li-enriched nickel-manganese oxide electrodes [20]. Moreover, a coating layer of AlF 3 is proven to be very effective in suppressing the gas generation and swelling behavior of spinel Li 4 Ti 5 O 12 (LTO) anodes in Li-ion batteries, thus allowing the improvement of their high-rate charge/discharge performance [21].…”
Section: Potential Applications and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Such problems can be solved by utilizing fluoride coated cathode. On the one hand, the common electrolyte in LIBs is LiPF 6 , F − can effectively inhibit the occurrence of interfacial side effects [94] ; on the other hand, it is found that the addition of F − can reduce the charge transfer resistance, improve the conductivity, and thus improve the rate performance and cyclability of the cathode material [107] . The typical fluorides as surface coating include LiF [108] , MgF 2 [109] , AlF 3 [110] , CaF 2 [111] , YF 3 [112] , and LaF 3 [113] .…”
Section: Fluoridementioning
confidence: 99%
“…Metal fluorides (MF x ) are one of the most attractive cathode candidates for lithium batteries because of their high conversion potential and large specific capacity, and for the high ionic nature of MF 3 cathodes, FeF 3 , TiF 3 , VF 3 and MnF 3 have been widely studied [18,19]. Aluminum fluoride (AlF 3 ) is a new type of promising cathode material with a high theoretical specific capacity (957 mAh g −1 ), abundant reserve and stable properties [20]. In this work, the lithium primary battery is assembled using AlF 3 as the cathode, lithium metal as the anode and 1 M LiPF 6 in dimethyl carbonate (DMC) and ethylene carbonate (EC) (1:1 in volume) with different contents of FEC as the electrolyte.…”
Section: Introductionmentioning
confidence: 99%